Penguatan Literasi Budaya pada Anak Melalui Film Animasi Danau Dendam Tak Sudah di Karang Indah Kecamatan Selebar Kota Bengkulu - Siti Nurjanah Siti; Nelda Sari Siregar; Selly Nopriani; Siti Yulfia; Siska Rahma Juwita; Tisen Meinandar (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Cultural literacy plays an important role in helping younger generations recognize and understand local cultural identity amid the rapid development of digital technology. However, the increasing use of digital entertainment media has caused children to become less familiar with local folklore, including the Danau Dendam Tak Sudah legend in Bengkulu. This community service activity aimed to strengthen children's cultural literacy through the use of the Danau Dendam Tak Sudah animated film as a local cultural learning medium in RT 19, Karang Indah Village, Selebar District, Bengkulu City. The method used in this program was the Asset Based Community Development (ABCD) approach, which consisted of the stages of discovery, dream, design, and destiny. Data were collected through observation, interviews, documentation, and evaluation using pretests and posttests involving 15 participants. The results showed an improvement in participants’ understanding of folklore and local cultural values. The average participant score increased from 5.53 in the pretest to 8.33 in the posttest, indicating an improvement of 28%. In addition, participants demonstrated positive enthusiasm during the film screening and discussion sessions. This activity indicates that audiovisual media based on local folklore can serve as an engaging and accessible cultural learning alternative to improve children’s cultural literacy.